Features of ultrasound and dopplerometric endometry examination in autoimmune thyroiditis patients with abnormal uterine bleeding - Alieksieieva, O.; Lazurenko, V.; Vasylieva, I.; Afanasiev, I.; Kudin, I.; Harkavenko, K. (Journal of Education, Health and Sport, 2022)
Abnormal uterine bleeding occurs in 10–30% of reproductive age women. Ultrasound examination is one of the most effective methods of diagnosing lesions of the pelvic organs while it has high sensitivity (96%), but low specificity (13.8%) in relation to endometrial lesions, the informativeness of ultrasound in the diagnosis of abnormal uterine bleeding ranges from 60 to 93.3%. It had been revealed revealed that the imbalance of thyroid hormones can have a direct effect on the endometrium. Thus, the analysis of ultrasound examinations data together with dopplerometric assessment of the blood flow of the internal genital organs in autoimmune thyroiditis patients with abnormal uterine bleeding is an urgent task of modern gynecology. The purpose is to determine the features of ultrasound exanimation with Doppler assessment of the endometrium in autoimmune thyroiditis patients with abnormal uterine bleeding. Materials and methods. The patients’ examinations were carried out from 2019 to 2022 We examined 120 patients, of whom 90 (75%) suffered from abnormal uterine bleeding and 30 (25%) did not have signs of gynecological and somatic pathology (control group). Abnormal bleeding patients average age was 36.3±3.2 years. The average age of bleeding and thyroid pathology women was 34.8±2.6 years, the control group average age was 30.7±2.9 years. Results. Echographic signs of endometrium structural changes were detected in 83 (92.2%) of abnormal nautoimmune bleeding women and in 7 (7.8%) women ultrasound signs of pathology were not detected. Significant differences were found when analyzing the results of ultrasonographic examination of patients with bleeding and bleeding + thyroid pathology. Conclusion. Ultrasound is an important method that contributes to a significant improvement in the diagnosis of isolated or combined benign uterine diseases in women with abnormal autoimmune bleeding at the background of thyroid pathology, and in most cases corresponds to the histological diagnosis.